(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Lung cancer was the most commonly diagnosed cancer as well as the leading cause of cancer death in males in 2008 globally Lung cancer is one of the most deadly tumours known. It is accurately found by many radiographic testing methods occasionally initiated for an unrelated silment. In light of new histology guided therapeutic modalities and lung cancer genetic categorization, histological characterisation of lung cancer has risen in prominence. The study was carried out to evaluate the correlation of clinical, radiological and histopatholgicalpattern of bronchial carcinoma. Methods: This observational cross sectional study was carried out in the Department of Medicine (Respiratory wing) Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Chest Disease (NIDCH) during the period of September 2011 to February 2012. A total of 60 admitted patients with a clinical, radiological and histological diagnosis of bronchial carcinoma were enrolled in the study. Complete sociodemographic characteristics, smoking status, radiological, and histopathological characteristics of the tumor were recorded in the study. CT scan of the chest was done in the majority of the patient. CT-guided FNAC and US guided FNAC tissue sampling from lung lesions followed by histopathological examination was done to diagnose the appropriate tumor type. After collecting the data, the statistical analyses were performed using the licensed version of Statistical Package for the Social Science Version 23 (SPSS-23). The p value <0.05 was considered as statistically significant. Results: Out of 60 cases, majority 27 (45.0%) patients were belonged to age 51 to 60 years with mean age was 58.4±10.2 years Male: female ratio was 4.1. Three fourth (75.0%) of the patients were smoker. Almost three fourth (73.3%) were right sided lesion and 26.7% were left sided lesion. In x-ray findings, 35.0% was found effusion followed by 31.7% consolidation, 15.0% consolidation & effusion (15%), 100% collapse & consolidation and 8.3% collapse. Squamous cell carcinoma (50.0%) was the most common histological pattern of bronchial carcinoma followed by adenocarcinoma (45.0%) and small cell carcinoma (5.0%). Diagnostic procedure of bronchial carcinoma was bronchoscopy & biopsy (15.0%), followed by CT guided FNAC (50.0%), US guided FNAC (5.0%), pleural biopsy (5.0%), lymph node biopsy (20.0%) and pleural fluid (5%). Significant association was found between cough, chest pain, face & neck swelling and histological type (p<0.05). Physical findings such as anaemia, clubbing, palpable lymph node, features of SVC obstraction, feature of consolidation, features of pleural effusion, features of collapse and hepatomegaly were significantly associated with histological type (p<0.05). Regarding X-ray findings, consolidation, fusion and collapse & consolidation were significantly associated with histological type (p<0.05). Conclusion: The results of this study showed that some correlation of clinical presentation with radiological and histopathological pattern of bronchial carcinoma. In this study found association found between histological type with cough, chest pain, face and neck swelling, anaemia, clubbing. palpable lymph node, features of SVC obstruction, consolidation, feature of pleural effusion and collapse and hepatomegaly. This study also found association between histological type with following radiological findings such as consolidation, effusion and collapse & consolidation. J. Dhaka National Med Coll. Hos 2023; 29 (01): 12-19